BODY IMAGE SATISFACTION, DISTRESS AND RESILIENCE IN WOMEN WITH BREAST CANCER SURGERY: A WITHIN GROUP STUDY - Mushtaq, Mamoona; Naz, Fauzia (Journal of Postgraduate Medical Institute, 2017)
Objectives: To explore the relationship among body shape satisfaction, distress and resilience in women with breast surgery and to explore the predictors of resilience in women with breast surgery. Methodology: The study was conducted in Shaukat Khanum Memorial Cancer Hospital and Research Center, Lahore and Inmol Cancer Hospital, Lahore. The current research was carried out by using within-subject research design. Sample comprised of 100 indoor patients admitted for general surgery. Age range of the sample was from 40 to 65 years. Body Image Satisfaction Scale (Cash, 2000), was used for assessing body image satisfaction , Depression, Anxiety, Stress Scale (Lovibond & Lovibond, 1995) for measuring distress and Hiew's State-Trait Resilience Checklist (2000) was used to measure resilience of the research participants. Results: In pre assessment, the mean scores of body image satisfaction were higher than post assessment. Similarly, scores were higher on distress and resilience on pre-testing as compared to post-testing. Scores on body image satisfaction and resilience in women with lumpectomy were higher than women with mastectomy. Conclusion: There were significant differences on body image satisfaction, distress and resilience in pre and post assessment of women with breast cancer surgery.